Economic, social and environmental disclosure, a theoretical framework and its application in Vietnam - Viet Ha TRAN VU; Anh MAI; Cam Tu DOAN; Benoît PIGÉ (Universitas Hayam Wuruk Perbanas, 2014)
This study focuses on the appraisal of firms’ performance and on its representation and reporting. Using interviews and inquiries in firms operating in the cement industry in Vietnam, two points are investigated. First, whether firms’ top executives consider that firms’ sustainable performance may include economic, social or environmental performance that is not integrated in financial statements. The theoretical framework is the stakeholder theory complemented with the institutional theory. Second, whether economic, social and environmental performance should be disclosed to answer the expectations of the various stakeholders. Therefore, our research contributes to corporate governance studies by focusing on reporting dedicated to all the stakeholders.